Mô hình hỗ trợ đa tầng (MTSS) trong giáo dục hòa nhập: Nghiên cứu thực trạng và đề xuất biện pháp triển khai ở các trường tiểu học tại thành phố Hà Nội - Đào, Thị Thu Thủy; Lâm, Thị Hoa; Nguyễn, Thanh Bảo Uyên (Tạp chí Giáo dục, 2025)
Inclusive education in Vietnam has been expanding; however, there is no unified framework for organizing support according to students’ levels of need. The Multi-Tiered System of Supports (MTSS) is an effective approach that integrates academic, behavioral, and social-emotional supports, yet it has not been systematically examined at the primary school level. This study surveyed 241 teachers from 23 primary schools in Hanoi, combined with interviews and classroom observations. Results indicate that universal supports are relatively well implemented (application of UDL, diversified teaching methods). Targeted supports remain limited and largely depend on individual teacher initiatives. Intensive supports are rarely implemented due to a lack of standardized guidelines, time constraints, and weak coordination mechanisms. The findings highlight a gap between policy and practice in MTSS implementation. It is essential to develop standardized implementation guidelines, enhance teacher professional development, and establish dedicated monitoring-support teams to improve effectiveness, thereby fostering sustainable inclusive education in primary schools.